ADVANTAGES OF REDUCING THERAPY OF ENDOMETRIOD CYSTS BY COMPARISON WITH LAPAROSCOPIC EXCISION BEFORE IVF PROGRAMS - Семен Вадимович Зотов; Полина Юрьевна Мотырева; Виталий Михайлович Кулешов; Борис Исаевич Айзикович; Виктория Васильевна Лихачева; Сергей Николаевич Филимонов (Медицина в Кузбассе)
The aim of the research: to evaluate the effect of transvaginal punction of the endometrioid cyst on the ovarian reserve of patients with infertility.